Epilepsy and Intellectual Disabilities - Prasher, Vee P.; Kerr, Mike (Springer London : Imprint: Springer, 2008)
Epilepsy and Intellectual Disabilities brings together findings from research and clinical practice, with comprehensive coverage of the important aspects of epilepsy in persons with intellectual disabilities. It is crucial for professionals involved in the care of persons with all intellectual disabilities to have a broad understanding of the essential range of issues, and therefore this book provides a truly multi-disciplinary perspective, complete with many figures and illustrations to underline the key points. Undoubtedly, research and clinical practice is much more advanced in the general population than in persons with intellectual disabilities, and so it is important that professionals and academics in the field of intellectual disabilities are made fully aware of ongoing developments in the general population, which will more likely than not become relevant to the intellectually disabled population. Through experience, this book also acknowledges that the impact on the person themselves and on their carers always needs to be taken into account, with treatment programs established with a multi-faceted team approach in mind. Avoiding the jargon of many titles in this area while maintaining the hands-on approach of clinical practice, this book meshes the practical and scientific worlds, with all chapters written by leading experts in the field.  .